1998
DOI: 10.1136/bjo.82.4.392
|View full text |Cite
|
Sign up to set email alerts
|

Open lacrimal surgery: a comparison of admission outcome and complications after planned day case or inpatient management

Abstract: Aims-To assess the outcome, in terms of completion of admission and complication rates, for two series of patients undergoing open lacrimal surgery, one group planned for a day case admission and the other planned for inpatient stay. Methods-A retrospective analysis of case notes was performed for 200 patients planned to have day case admission (for 209 open lacrimal operations) and the details compared with those for 200 inpatient admissions (for 228 lacrimal procedures) during the same period of study. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Nausea and epistaxis were the most frequent complications that prompted patients to present to the hospital, and various studies have reported the incidence of such complications as 0.5–4.0% (Dresner et al. 1991; Hanna et al. 1998; Tsirbas & McNab 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nausea and epistaxis were the most frequent complications that prompted patients to present to the hospital, and various studies have reported the incidence of such complications as 0.5–4.0% (Dresner et al. 1991; Hanna et al. 1998; Tsirbas & McNab 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Dacryocystorhinostomy on an outpatient basis is generally accepted as a safe procedure. Nausea and epistaxis were the most frequent complications that prompted patients to present to the hospital, and various studies have reported the incidence of such complications as 0.5-4.0% (Dresner et al 1991;Hanna et al 1998;Tsirbas & McNab 2002). A study conducted on 112 patients between the ages of 70 and 90 reported no serious complications following external DCR (Hurwitz et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies show that the percentage of patients who have undergone bilateral DCR varies between 9% and 18%. [3][4][5][6][7][8] *This study was presented at the 28th Annual Meeting of European Society of Ophthalmic and Plastic Surgery, Munich, Germany, September 9-11, 2010. Correspondence: Dilek Yuksel, Ministry of Health, Ankara Training and Research Hospital, Department of Ophthalmology, Ankara, Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure has remained largely unchanged since, with improvement in success rates largely due to advances in suture materials, anaesthesia and instruments. The external DCR, the procedure by which all other techniques are judged, gives a success rate of between 90 and 95%4 5 6 7 although the occasional modern study still shows success rates around 75% 8…”
mentioning
confidence: 99%